2022
DOI: 10.1111/acel.13588
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cdc42 signaling by the dopamine D2 receptor in a mouse model of Parkinson’s disease

Abstract: Substantial spine loss in striatal medium spiny neurons (MSNs) and abnormal behaviors are common features of Parkinson's disease (PD). The caudate putamen (CPu) mainly contains MSNs expressing dopamine D1 receptor (dMSNs) and dopamine D2 receptor (iMSNs) exerting critical effects on motor and cognition behavior. However, the molecular mechanisms contributing to spine loss and abnormal behaviors in dMSNs and iMSNs under parkinsonian state remain unknown. In the present study, we revealed that Cell division cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
(94 reference statements)
0
8
0
Order By: Relevance
“…per mL. These promoters can initiate the expression of target proteins specifically in D1-MSNs or D2-MSNs of the NAc, as reported by previous research ( Ying et al, 2022 ).…”
Section: Methodsmentioning
confidence: 64%
“…per mL. These promoters can initiate the expression of target proteins specifically in D1-MSNs or D2-MSNs of the NAc, as reported by previous research ( Ying et al, 2022 ).…”
Section: Methodsmentioning
confidence: 64%
“…Interestingly, among the 159 identified risk genes for PD, several are enriched in these PD-related pathways. For example, genes such as SCNA, CDC42 ( Ying et al, 2022 ), EFNA1, MAPT ( Aarsland et al, 2017 ), and LZTS3 ( Li et al, 2023 ). Specifically, overexpressed SCNA, which codes for the protein alpha-synuclein, displayed aberrant synaptic nucleoprotein aggregation, causing neurotoxicity and neuronal death in PD ( Rocha et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This reduction ultimately leads to a decrease in the unnecessary elimination of dopamine neurons. Therefore, CDC42 inhibitors hold promise as a potential alternative for the treatment of PD ( Surviladze et al, 2010 ; Barcia et al, 2012 ; Ying et al, 2022 ). These findings provide valuable clues for in-depth research into their association and role in PD, indicating the need for further comprehensive investigation into PD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there is a number of potential genetic or biological association between IQ and PD. For example, CDC42, the corresponding gene of rs10917152, is associated with PD ( Ying et al, 2022 ). It has been shown that impaired CDC42 signaling regulated by dopamine D2 receptors leads to spine loss and behavioral deficits in PD ( Ying et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, CDC42, the corresponding gene of rs10917152, is associated with PD ( Ying et al, 2022 ). It has been shown that impaired CDC42 signaling regulated by dopamine D2 receptors leads to spine loss and behavioral deficits in PD ( Ying et al, 2022 ). ESSRG (a transcription factor estrogen-related receptor gamma), the corresponding gene of rs10779271, deficiency leads to the reduction of genes related to synaptic, mitochondrial function, and autophagy, which causes PD ( Fox et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%